The importance value index of the flora in the green belt of the Sultan Azlan Shah Campus, Universiti Pendidikan Sultan Idris, Perak, Malaysia - Mohmadisa Hashim (Tanjong Malim, 2019)
The importance value index of the flora in the green belt of the Sultan Azlan Shah Campus, Universiti Pendidikan Sultan Idris, Perak, Malaysia by Mohmadisa Hashim